The comparison of intelligence quotients of atopic and nonatopic children in Ibadan, Nigeria - Daramola O O M; Ayoola O; Ogunbiyi A (Wolters Kluwer Medknow Publications, 2010)
Background: Atopy-related illnesses such as atopic dermatitis and asthma are chronic illnesses, and children suffering from such illnesses are subjected to frequent absenteeism from school. Studies have shown that the performance of children with asthma was comparable to their healthy counterparts despite their absenteeism at school, in contrast to findings in other chronic illnesses like epilepsy. Aim: In the present study, we investigated the association between atopy and intelligence quotient (IQ) scores in a group of Nigerian children in Ibadan, a city in southwestern Nigeria. Materials and Methods: This is a cross-sectional study of children in an urban elementary school. Questionnaires to ascertain the presence of atopy-associated conditions such as hay fever, atopic dermatitis, asthma, allergic rhinitis, and allergic conjunctivitis were administered to the parents of 128 pupils in the 3 rd to 6 th grades of elementary school. Based on the responses to the questionnaire, pupils were categorized as being atopic and nonatopic. All the pupils underwent the Standard Progressive Matrices IQ test. The IQ scores were then compared among these two groups of children. Results: Out of the children studied, 26.6% were found to have atopy and after adjusting for factors such as age and sex, the IQ scores in this atopic group were not found to be statistically different from the scores in the nonatopic group (r = 2.122872, P = 0.009). Conclusion: IQ scores were not statistically significantly different for children with and without atopy. Thus, the presence of atopy does not appear to be associated with low IQ scores and hence, may not be related to poor school performance.